MENELAAH KESALAHAN EJAAN PADA KARYA ILMIAH (MAKALAH) MAHASISWA SEMESTER I KOMUNIKASI PENYIARAN ISLAM IAIN TAKENGON - Alsabarni Alsabarni (Jurnal Pendidikan, Bahasa dan Budaya, 2022)
Papers are one of the daily tasks for students. There are still many student papers that are not in accordance with the EYD or vocabulary in the KBBI. This research focuses on how the form of errors in writing capital letters, writing hyphens, punctuation marks, and standard language in scientific papers (papers) of students, especially the IAIN Takengon KPI Study Program. This study aims for KPI (Islamic Broadcasting Communication) undergraduate students to be trained in good and correct writing skills in accordance with spelling rules. The approach used in this research is qualitative with descriptive method. The results of the research conducted, the researcher found spelling errors in the contents of the paper, namely: (1) there were 15 capital letter writing errors, (2) there were 20 mistakes in the location of conjunctions, (3) there were 10 non-standard language errors, (4) writing errors there are 20 punctuation marks (colons, commas, quotation marks, punctuation marks).